DETEKSI FORMALIN PADA IKAN DAN SEAFOOD ASIN DARI BEBERAPA PASAR LOKAL DI KOTA SAMARINDA, KALIMANTAN TIMUR - Irwan Ramadhan Ritonga; Ristiana Eryati; Akhmad Rafii (Jurnal Inovasi Pendidikan dan Sains, 2022)
Formalin is a chemical compound that is often added to fish and seafood. When formalin exposure enters the human body, it is very dangerous for human health. The purpose of this study was to detect the formalin content in fish and seafood samples from several local markets in the city of Samarinda. The research method was descriptive observational on 149 test samples of fish and seafood salted. Detection of formalin content in fish and seafood was detected by the rapid test kit. When the test sample changed to red and purple color, the sample was indicated to be positive for formalin. It was found that 10 out of 13 fish samples and 4 out of 4 seafood samples were positive for formaldehyde. The types of fish and seafood containing formalin in this study were layang, sarden, teri, baronang, pedak, haruan laut, kepala batu, kaca-kaca, tenggiri, hiu, cumi, udang ebi, udang papay and baby cumi. This study suggests that consumers should be more careful to buy fish and seafood that contain formaldehyde.